1993
DOI: 10.1084/jem.178.2.597
|View full text |Cite
|
Sign up to set email alerts
|

P58 molecules as putative receptors for major histocompatibility complex (MHC) class I molecules in human natural killer (NK) cells. Anti-p58 antibodies reconstitute lysis of MHC class I-protected cells in NK clones displaying different specificities.

Abstract: SummaryHuman CD3-16 + 56 § natural killer (NK) cells have been shown to display a donaUy distributed ability to recognize major histocompatibility complex (MHC) class I alleles. Opposite to T lymphocytes, in NK cells, specific recognition of MHC class I molecttles appears to induce inhibition of cytolytic activity and, thus, to protect target cells. Since a precise correlation has been established between the expression of the NK-specific GL183 and EB6 surface molecules (belonging to the novel p58 molecular fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
337
1
7

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 492 publications
(351 citation statements)
references
References 27 publications
(94 reference statements)
6
337
1
7
Order By: Relevance
“…Initial studies indicated a simple bipartite system in which KIR2DL2/3 recognizes HLA‐C allotypes with asparagine at residue 80 (the HLA‐C1 motif), and KIR2DL1 recognizes HLA‐C allotypes with lysine at residue 80 (the HLA‐C2 motif). Dimorphism at residue 44 of the KIR molecule causes these specificity differences, where KIR2DL2/3 has lysine and KIR2DL1 has methionine 36, 100, 104, 105. Crystal structures showed that K44 of KIR2DL2 forms a hydrogen bond with the N80 of HLA‐C1 99.…”
Section: Kir Ligand Bindingmentioning
confidence: 99%
“…Initial studies indicated a simple bipartite system in which KIR2DL2/3 recognizes HLA‐C allotypes with asparagine at residue 80 (the HLA‐C1 motif), and KIR2DL1 recognizes HLA‐C allotypes with lysine at residue 80 (the HLA‐C2 motif). Dimorphism at residue 44 of the KIR molecule causes these specificity differences, where KIR2DL2/3 has lysine and KIR2DL1 has methionine 36, 100, 104, 105. Crystal structures showed that K44 of KIR2DL2 forms a hydrogen bond with the N80 of HLA‐C1 99.…”
Section: Kir Ligand Bindingmentioning
confidence: 99%
“…Inhibitory NK-cell receptors specific for classical MHC class I molecules belong to the mouse Ly49 (also known as KLRA) receptor family 6,7 and the human killer immunoglobulin-like receptor (KIR) family [8][9][10] . The molecular cloning of NK-cell receptors led to the identification of additional MHC class I receptors, which had not been predicted on the basis of functional experiments: human leukocyte immunoglobulin-like receptors (LILRs; also known as LIRs, ILTs or MIRs), and their orthologues, mouse paired immunoglobulin-like receptors (PIRs), as well as the heterodimeric CD94-NKG2 (NK group 2) receptors 11-14 (TABLE 1).…”
Section: 'Missing-self' Hypothesismentioning
confidence: 99%
“…2) and correlates well with their ability to inhibit NK cytolysis of target cells bearing those HLA allotypes. Specificity of inhibitory KIR for HLA-C allotypes is dictated to a large extent by the presence of asparagine or lysine at position 80 of the HLA-C molecule (3). KIR2DL1 recognizes group 2 HLA-C molecules, which have Lys 80 , whereas KIR2DL2 and KIR2DL3 prefer group 1 HLA-C molecules containing Asn 80 (3).…”
Section: ) Binding Of Inhibitory Kir (Designated 2dlmentioning
confidence: 99%
“…Specificity of inhibitory KIR for HLA-C allotypes is dictated to a large extent by the presence of asparagine or lysine at position 80 of the HLA-C molecule (3). KIR2DL1 recognizes group 2 HLA-C molecules, which have Lys 80 , whereas KIR2DL2 and KIR2DL3 prefer group 1 HLA-C molecules containing Asn 80 (3). Studies performed in vitro indicate that this division of specificity is not necessarily strict and may depend to some extent on bound peptide (4,5).…”
Section: ) Binding Of Inhibitory Kir (Designated 2dlmentioning
confidence: 99%